Pertanggungjawaban Hukum yang Berkeadilan terhadap Aparatur Pemerintah pada Kasus Pengadaang Barang dan Jasa - Kukuh Tejomurti (Dialogia Iuridica, 2017)
This article describes the legal responsibility for the government officials involved lawsuit of the procurement of goods and services. Each year the government officials (budget users, official commitment maker, and procurement officer) is requiered to absorb optimally budget in order to succed the government development program, yet the other side they will experience â€œquandaryâ€ in the audit process by the Audit Board of The Republic Indonesia. the lower decree of checks and verification set off civil and administrative lawsuit attracted to the criminal responsibility. This causes the psichological effect for the government officials related to the procurement of goods and services. The problems researched: firstly, what is the factor causing the government officials of the procurement which will be able to involve law suit concerning on the corruption which has type of the financial harm state?; secondly, How is the legal responsibility for the government officials of the procurement fairly involved the corruption lawsuit having the type of the financial harm state. The research methods used by this research is the normative legal research applying the conceptual and legislation approach. The result of first discussion often find in the field of procurement officers and officials is a commitment-makers who are not competent in their field so the procurement process does not give good results and obey the law. The second result, law enfocer often has checked and verified a procurement lawsuit easily concerning in the corruption which has type of the financial harm state even though the facts found to be more civil and administrative